University experience and entrepreneurial quality development among students in Malaysian comprehensive university / Shamsul Huda Abd Rani...[et al.] - Abd Rani, Shamsul Huda; Mustafa Kamil, Bidayatul Akmal; Abd Rani, Shamsul Hana (Universiti Teknologi MARA, Kedah, 2019)
The impact of university experience in developing entrepreneurial quality among students from Comprehensive University in Malaysia is explained in this paper. The function of university experience is crucial in inculcating entrepreneurial quality among students in Higher Learning Education Institutions. Respondents in this study are undergraduate students from Comprehensive Universities in Malaysia. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 23.0. The result of the study indicates that university experience give impact to the development of entrepreneurial quality in higher learning institution particularly Malaysia university students. Eventually, it is hoped that in the future, more programs should be implemented in order to expose the students to the real career life that in turn can benefit them in terms of developing entrepreneurial quality.